Analisis kedisiplinan guru dalam proses pembelajaran di SMA Negeri 2 Purworejo: Studi Kualitatif - Suhanda, Suhanda; Hidayatullah, Ahmad Syauqi (Bulletin of Educational Management and Innovation, 2024)
Background: Teacher discipline is one of the important factors that play a role in the success of the learning process in schools. Teachers who are disciplined in carrying out their duties, both in administration, implementation of learning, and evaluation of learning, can create a conducive learning atmosphere and support the achievement of educational goals. Purpose: This study aims to describe (1) the characteristics of teacher discipline in learning administration; (2) the characteristics of teacher discipline in implementing learning; (3) the characteristics of teacher discipline in evaluating learning. Method: This study is descriptive qualitative research and was held at Senior High School 2 Purworejo. The interviewees are principal, vice principals, teachers and students. Method collection data used are observation, deep interview, and documentation. Data analysis was done with the use of analysis technique in site-organized. The triangulation was applied to seek for the data validity. Findings: The results of the study show that: (1) some teachers were still doing minor infringements or violation of the rules whether in related to administration, implementation or evaluation learning. Medium and heavy infringements or violation categories were not found in this study.  If it happened, the violator will be given a sanction as a criminal for heavy infringement or in the form of dismissal from the position; (2) The efforts which are undertaken by school for preventing the existence of infringements or violations done by the teachers is doing regulations socialization concerning the implementation of government employee or teachers discipline. Other efforts to do so are holding a teacher coaching periodically and continuously, and do supervision; (3) having high awareness among the teachers in not to do discipline infringement or violation causes the effectiveness in teaching and learning activities (KBM). This achievement is able to increase the teaching and learning quality.